Pengembangan Media Pembelajaran untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Sejarah Kebudayaan Islam di MTs Negeri 2 Surakarta - Mar’atin Mifbakhul Ma’rufi2; Hafidz Hafidz; Husna Nashihin (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
Quality education serves as the primary foundation for producing knowledgeable and competitive generations. The subject of Islamic Cultural History at MTs Negeri 2 Surakarta plays a significant role in introducing students to the rich values, history, and culture of Islam. However, students often face challenges in comprehending complex concepts within this subject. The development of effective learning media becomes a highly relevant solution for enhancing students' learning outcomes. This research aims to develop innovative learning media specifically designed for the Islamic Cultural History subject at MTs Negeri 2 Surakarta. This learning media is designed with consideration for student characteristics, curriculum requirements, and available resources. The research methodology employed is qualitative research with a case study approach. Data collection is conducted through interviews with subject teachers, classroom observations, and media learning trials with students. The research findings indicate that the development of learning media tailored to student characteristics and subject matter can enhance students' interest in learning, their comprehension of concepts, and overall learning outcomes. The interactive learning media developed provide a more engaging and effective learning experience for students. Furthermore, teachers play a crucial role in supporting the effective use of this learning media in day-to-day teaching.